Challenges and opportunities associated with cervical cancer screening programs in a low income, high HIV prevalence context - Adebola Adedimeji; Rogers Ajeh; Amanda Pierz; Relindis Nkeng; Jackson Jr. Ndenkeh; Norbert Fuhngwa; Denis Nsame; Miriam Nji; Anastase Dzudie; Kathryn M. Anastos; Philip E. Castle (BMC, 2021)
Abstract Background Cervical cancer is a leading cause of death among Cameroon women. The burden of cervical cancer is in part traceable to the inadequate understanding of socio-contextual determinants of access to screening and prevention opportunities. We explored multilevel individual, community and structural factors that facilitate or inhibit cervical cancer prevention in women at risk in a low-income, high HIV prevalence context. Methods We utilized an exploratory qualitative approach to obtain data through focus group discussions and in-depth interviews from May to August, 2018. A two-stage purposive sampling strategy was used to select 80 women and 20 men who participated in 8 focus group discussions and 8 in-depth interviews. The socio-ecological model guided data analyses to identify micro-, meso-, and macro-level determinants of cervical cancer screening. Results Micro-level factors including lack of awareness and knowledge about cervical cancer, lack of access to information, excessive cost of cervical cancer screening, low risk perceptions, and poor health seeking behaviors were major barriers for women seeking cervical cancer screening. Meso-level factors, such as social networks, socio-cultural norms, perceptions of the role of men and HIV-related stigma when screening is integrated into HIV care, also engender negative attitudes and behaviors. Macro-level barriers to cervical cancer screening included poorly equipped health facilities and a lack of national cancer prevention policies and programs. Conclusion In the context of the call for elimination of cervical cancer as a public health problem, our findings highlight challenges and opportunities that should be considered when implementing interventions to increase uptake of cervical cancer screening in low-middle income settings.